Application of sensory evaluation, GC-ToF-MS, and E-nose to discriminate the flavor differences among five distinct parts of the Chinese blanched chicken. (November 2020) - Xu, Yuan; Chen, Yan Ping; Deng, Shaolin; Li, Chunbao; Xu, Xinglian; Zhou, Guanghong; Liu, Yuan
Graphical abstract: Highlights: Breast meat was rated more chicken-like than other parts, and evoked more positive emotions from consumers. The re-heated processing of CBC should be optimized to avoid the undesired flavor particularly from butt and head. Separately packed breast could be provided from manufacture to cater consumers. Abstract: Blanched chicken, boiling the whole chicken without removing head and butt parts during process, is a traditional poultry product in China. In this manuscript, the flavor differences of five parts (skin, breast, thigh, head and butt) of the Chinese blanched chicken (CBC) were studied using sensory evaluation and instrumental analysis. Check-all-that-apply (CATA), rate-all-that-apply (RATA), and 9-point hedonic preference were used to collect consumers' sensory results. Gas chromatograph-time of flight mass spectrometer (GC-ToF-MS) and electronic nose (E-nose) were used to discriminate flavor variances. CATA perceptions showed different parts of CBC stimulated consumers' odor and emotion feelings differently. GC-ToF-MS and E-nose data elaborated that the flavor of breast with chicken-like flavor was better than the other parts. Consumers preferred the chicken breast part the most. This analysis of different parts of CBC could provide advice to cater consumers' preference and predict the quality change might induce.